Conformity of Human Papillomavirus between Self-examination of Vaginal Fluid and Cervical Specimen with Fluid-Based Cytology in Precancerous Lesions: Tingkat Kesesuaian Human Papillomavirus antara Pemeriksaan Cairan Vagina secara Mandiri dan Spesimen Serviks dengan Sitologi Berbasis Cairan pada Lesi Prakanker - Rahmawaty Anwar; Syahrul Rauf; Eddy R. Moeljono (Indonesian Journal of Obstetrics and Gynecology, 2018)
Abstract Objective: To determine the conformity of human papillomavirus between self-examination of vaginal specimen and cervical specimen with fluid-based cytology in precancerous lesions. Methods: A cross-sectional study performed on cervical and vaginal fluid from 90 pre-cancerous lesions patients from April to September 2016. Cytological examination performed with self-examination and liquid-based cytology technique. HPV genotyping performed with PCR technique. Data were analyzed with SPSS. Results: Most of the women aged >35 years (89%), 78% (71/90) multiparity and 74.4% (67/90) do not know about HPV screening. High risk type found in both vaginal and cervical fluid was type 16, 18, 33 and 45 whereas type 35 found only in vaginal fluid. The most prevalent high-risk HPV for both specimens were type 16 and 18. HPV type 42 and 53 were the low risk HPV found in the vaginal and cervical specimens (table 2). Cohen’s kappa for inter-test agreement shows a strong correlation (r=0.864). Conclusion: The HPV self-examination method can be used as a primary examination of cervical cancer lesions detection in addition to fluid-based cytology with the similar results. Keywords: Human papillomavirus, self-examination, fluid-based cytology, cervical cancer Abstrak Tujuan: Untuk mengetahui tingkat kesesuaian antara pemeriksaan HPV mandiri dari spesimen vagina dan hasil pemeriksaan sitologi berbasis cairan dari spesimen serviks. Metode: Penelitian cross-sectional dilakukan pada cairan serviks dan vagina dari 90 pasien lesi pra-kanker pada April sampai September 2016. Pemeriksaan sitologi dilakukan dengan pemeriksaan diri dan teknik sitologi berbasis cairan. Pemeriksaan genotip HPV dilakukan dengan teknik PCR. Data dianalisis dengan SPSS. Hasil: Sebagian besar wanita dalam penelitian iniaberusia >35 tahun (89%), 78% (71/90) multiparitas dan 74,4% (67/90) tidak mengetahui tentang skrining HPV. Tipe HPV risiko tinggi yang ditemukan pada cairan vagina dan serviks adalah tipe 16, 18, 33 dan 45 sedangkan tipe 35 hanya ditemukan pada cairan vagina. Tipe HPV risiko tinggi yang dominan untuk kedua spesimen adalah tipe 16 dan 18. HPV tipe 42 dan 53 adalah HPV risiko rendah yang ditemukan pada baik spesimen vagina maupun serviks. Kappa Cohen untuk tingkat kesesuaian antara pemeriksaan mandiri dan sitologi berbasis cairan menunjukkan korelasi kuat (r = 0,864). Kesimpulan: Metode pemeriksaan HPV secara mandiri sendiri dapat digunakan sebagai pemeriksaan primer deteksi lesi kanker serviks selain sitologi berbasis cairan dengan hasil yang sama.